STUDI TENTANG LOYALITAS MEREK - Bayu Gustiko, Ardian; Widiyanto, Ibnu (Diponegoro Journal of Management, 2015)
This study is to investigate why consumers repuchase the products of House of Moo Cafe. This research analyzes and provides empirical evidence on whether product quality and the brand image of impact on brand attitude in improving brand loyalty . Sample of this research are house of moo consumers with 250 people by using non probability sampling techniques. Data analysis methods used are quantitative analysis, reability and validity, classic test assumptions, hypothesis test , coefficient determinan, linear regression analysis as well as test sobel. The result showed that product quality and brand image have a positive towards to brand attitude and product quality, brand image and brand attitude have a positive towards to brand loyalty. The result of sobel test showed brand attitude that mediates between being variable product quality and brand loyalty. Brand attitude that mediate between brand image to brand loyalty.